Number experiment at researches of centrifugal pumps - Sutorma Игорь Иванович; Lifanov А. В.; Skidan Д. М. (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The authors propose an experimental method of investigating hydrodynamic process in the chamber of centrifugal pumps with the aim of their construction improvement. The results of number experiment for modeling nominal operation modes of fire-fighting pump PN-40U are given in the article.